2010
DOI: 10.1074/jbc.m110.156950
|View full text |Cite
|
Sign up to set email alerts
|

O-Glycosylation Modulates Proprotein Convertase Activation of Angiopoietin-like Protein 3

Abstract: The angiopoietin-like protein 3 (ANGPTL3) is an important inhibitor of the endothelial and lipoprotein lipases and a promising drug target. ANGPTL3 undergoes proprotein convertase processing (RAPR 224 2TT) for activation, and the processing site contains two potential GalNAc O-glycosylation sites immediately C-terminal (TT 226 ). We developed an in vivo model system in CHO ldlD cells that was used to show that O-glycosylation in the processing site blocked processing of ANGPTL3. Genome-wide SNP association stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(66 citation statements)
references
References 42 publications
4
62
0
Order By: Relevance
“…FGF23 PC-processing site, are not glycosylated by the endogenous GalNAc-Ts expressed in both CHO-K1 and ldlD cells (11,12). Although we could not directly confirm glycosylation of the P1Ј-P4Ј constructs by mobility shifts, the finding that constructs P1Ј-P3Ј exhibited complete or partial blocking of processing is in accord with efficient glycosylation of the target sequences.…”
Section: Ex Vivo Analysis Of Pc Processing In the Cho Ldld Cell Model-mentioning
confidence: 38%
See 3 more Smart Citations
“…FGF23 PC-processing site, are not glycosylated by the endogenous GalNAc-Ts expressed in both CHO-K1 and ldlD cells (11,12). Although we could not directly confirm glycosylation of the P1Ј-P4Ј constructs by mobility shifts, the finding that constructs P1Ј-P3Ј exhibited complete or partial blocking of processing is in accord with efficient glycosylation of the target sequences.…”
Section: Ex Vivo Analysis Of Pc Processing In the Cho Ldld Cell Model-mentioning
confidence: 38%
“…We used a modification of a previously described chimeric reporter construct that facilitates rapid selection of stable clones as well as screening of processing and analysis of the influence of O-glycosylation ( Fig. 2A) (12). We initially analyzed glycosylation and processing of the reporter constructs by transient expression, but found that both glycosylation and processing of secreted products were quite incomplete so we used stable clones for all studies reported (Fig.…”
Section: Ex Vivo Analysis Of Pc Processing In the Cho Ldld Cell Model-mentioning
confidence: 99%
See 2 more Smart Citations
“…This effect also seems LPL-specific (26). ANGPTL3 cleavage is reported to be affected by the O-glycosylation state of threonine at amino acid position 226 by polypeptide N-acetylgalactosaminyltransferase 2, adjacent to the proprotein convertase-processing site (27). However, this O-glycosylation site is not conserved among ANGPTL4 proteins.…”
Section: Discussionmentioning
confidence: 97%